2012
DOI: 10.1007/s00265-012-1316-5
|View full text |Cite
|
Sign up to set email alerts
|

Chick-a-dee call variation in the context of “flying” avian predator stimuli: a field study of Carolina chickadees (Poecile carolinensis)

Abstract: Chick-a-dee calls function in social organization in Poecile (chickadee) species. Recent field and aviary studies have found that variation in chick-a-dee calls relates to the type or proximity of avian predator, or level of threat. Earlier studies on calls in the context of predator stimuli have typically used stationary and perched predator models. For chickadees and other small songbirds, more frequently detected and more dangerous avian predatory stimuli are flying predators. In the present study, we teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In addition to the anti-predator findings presented in the introduction, there have been other studies demonstrating a connection between predator presence and vocalizations. In Carolina chickadees, Poecile carolinensis, note usage in chick-a-dee calls varies in relation to predator behavior: Calls produced in contexts of perched avian predator models contain relatively more D notes (Soard and Ritchison 2009), whereas calls produced in contexts of flying avian predator models contain relatively more Introductory notes (Zachau and Freeberg 2012). A recent study found that calling and foraging behavior of tufted titmice were sensitive to the facial orientation of a potential threat-a mask-wearing human observer standing near a feeding station being used by birds (Freeberg et al 2014)-but that potential threat was clearly artificial.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the anti-predator findings presented in the introduction, there have been other studies demonstrating a connection between predator presence and vocalizations. In Carolina chickadees, Poecile carolinensis, note usage in chick-a-dee calls varies in relation to predator behavior: Calls produced in contexts of perched avian predator models contain relatively more D notes (Soard and Ritchison 2009), whereas calls produced in contexts of flying avian predator models contain relatively more Introductory notes (Zachau and Freeberg 2012). A recent study found that calling and foraging behavior of tufted titmice were sensitive to the facial orientation of a potential threat-a mask-wearing human observer standing near a feeding station being used by birds (Freeberg et al 2014)-but that potential threat was clearly artificial.…”
Section: Discussionmentioning
confidence: 99%
“…in press), we are increasingly able to make inferences about the potential messages associated with the different note types in the call. For example, for Carolina chickadees, A notes appear to be used in situations of heightened alarm, such as when an avian predator is detected flying in the area of chickadees (Freeberg 2008; Zachau & Freeberg 2012). The two populations here differ in their use of A notes in the flight context, with TENN birds less likely to use A notes in calls produced during flight, but no such differences are seen in INDI birds.…”
Section: Discussionmentioning
confidence: 99%
“…2005; Freeberg 2008; Mahurin & Freeberg 2009; Nolen & Lucas 2009; Soard & Ritchison 2009; Bartmess‐LeVasseur et al. 2010; Zachau & Freeberg 2012). Here, I will additionally use ‘context’ to refer to behavioral contexts and behavioral tendencies – namely the behavioral context of flight.…”
Section: Introductionmentioning
confidence: 99%
“…When an avian predator is detected flying through the area where chickadees are located, those chickadees produce many fewer D notes and tend to produce more introductory notes [82]. This finding from naturalistic observational research has been corroborated with a more recent experimental study [86]. When chickadees first detect food, they produce more D notes in their calls, and this variation in their calls can affect the behaviour of receivers during playback studies [87,88].…”
Section: Social and Vocal Complexity In The Paridaementioning
confidence: 95%